Outpatient Provider Concentration and Commercial Colonoscopy Prices - Alexis Pozen PhD (SAGE Publishing, 2015)
The objective was to evaluate the magnitude of various contributors to outpatient commercial colonoscopy prices, including market- and provider-level factors, especially market share. We used adjudicated fee-for-service facility claims from a large commercial insurer for colonoscopies occurring in hospital outpatient department or ambulatory surgery center from October 2005 to December 2012. Claims were matched to provider- and market-level data. Linear fixed effects regressions of negotiated colonoscopy price were run on provider, system, and market characteristics. Markets were defined as counties. There were 178 433 claims from 169 providers (104 systems). The mean system market share was 76% (SD = 0.34) and the mean real (deflated) price was US$1363 (SD = 374), ranging from US$169 to US$2748. For every percentage point increase in a system or individual facility's bed share, relative price increased by 2 to 4 percentage points; this result was stable across a number of specifications. Market population and price were also consistently positively related, though this relation was small in magnitude. No other factor explained price as strongly as market share. Price variation for colonoscopy was driven primarily by market share, of particular concern as the number of mergers increases in wake of the recession and the Affordable Care Act. Whether variation is justified by better quality care requires further research to determine whether quality is subsumed in prices.